Edukasi Pengelolaan Sampah melalui Papan Informasi Pada Masyarakat Kelurahan Pematang Gubernur - Oktaviani, Prisilia; Novita, Eni; Lorenza, Maya; Wibawa, Gempar; Abu, Rojeng Muhammad; Yanti, Rina Trisna; Syafran, Ahmad; Mujiono, Mujiono (Jurnal Gotong Royong, 2026)
Pematang Gubernur Subdistrict is one of the areas with well-organized residential areas and a fairly good level of environmental cleanliness awareness. However, understanding of waste management and separation is still uneven, and there are no information media available to help residents understand the proper way to sort household waste. This community service program aims to provide education through the installation of educational information boards in RT 22 RW 02, Pematang Gubernur Subdistrict. The implementation methods include field observation, preparation of educational content, media creation, board installation, and socialization to residents. The results of the activity show that visual educational media help increase public knowledge about types of waste and how to separate it, as well as serve as a sustainable educational tool accessible to residents.